2009
DOI: 10.1603/008.102.0418
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Heat Stress and Food Supply on Flight Performance of Olive Fruit Fly (Diptera: Tephritidae)

Abstract: The olive fruit fly, Bactrocera oleae (Rossi) (Diptera: Tephritidae), is a newly invasive pest of olives, Olea europaea L., in California. The table olive industry is located in California's Central Valley, where daily high summer temperatures can be >35.0°C. This study investigated the effects of high temperatures (heat stress) and food conditions on the flight performance of B. oleae in laboratory flight mill tests. Flies were provided food (honey and hydrolyzed yeast) and water for a 1-wk preconditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 35 publications
(39 reference statements)
2
30
0
Order By: Relevance
“…High density B. oleae populations occur in California's coastal olive regions while population density and crop infestation is generally lower in the interior valleys ) where high summer temperatures may limit population growth Wang et al 2009a). Studies of indigenous natural enemies in California found that B. oleae larvae are attacked by Pteromalus sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High density B. oleae populations occur in California's coastal olive regions while population density and crop infestation is generally lower in the interior valleys ) where high summer temperatures may limit population growth Wang et al 2009a). Studies of indigenous natural enemies in California found that B. oleae larvae are attacked by Pteromalus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Relative to climate, olives are grown in California's coastal regions that are characterized by mild temperatures and in interior valleys that are characterized by hot, dry summers. In the warmer interior valleys, fly population growth may be limited during periods of high summer temperature , which increases adult fly mortality and reduces their movement and oviposition success (Wang et al 2009a). This might also impact parasitoid establishment and effectiveness in California via direct mortality of Psyttalia as developing larvae or as foraging adults Sime et al 2006a;Yokoyama et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The olive fruit fly's survival is limited in regions with high or low temperature extremes (Wang, Johnson, Daane, Opp 2009). The fruit also may not be developed enough for olive fruit fly to survive early in the summer; young, hard fruit are not preferred for oviposition (Burrack and Zalom 2008).…”
Section: Releasing Natural Enemiesmentioning
confidence: 99%
“…Using a customdesigned flight mill, Wang et al (2009b) reported that adults of both sexes held for 7 days at 75°F (constant temperature) and provided with ample food (honey and hydrolyzed yeast) and water, were able to fly uninterrupted for an average of 2,164.8 ± 228.8 yards during a mean period of 1.54 ± 0.16 hours ( fig. 3).…”
Section: Marshall W Johnsonmentioning
confidence: 99%
“…Without food or water immediately available, an adult will only be able to fly an average of 16.4 ± 4.4 yards to locate these resources in a dry and unexplored landscape. Such a fl y would have an 84% chance of dying in the fi rst 24 hours, and of those that did survive only about 25% would be able to fl y (Wang et al 2009b). Additionally, when olive fruit fl y adults were held at 65°F at night and 95°F or 100°F during the day over a 3-day period with either water alone or no food or water, those fl ies that survived one day could fl y signifi cantly farther than those that survived 3 days (F 2,407 = 18.7, P < 0.01) (fi g. 4).…”
mentioning
confidence: 99%